Message Design Process in Shadow Puppet as Health Education Media (Phenomenology Study on Shadow Puppet Creation of Dr. Djoko Santoso, M.Kes DAHK) - Endry Putra; Bambang Dwi Prasetyo; Zulkarnain Nasution Nasution (Wacana Journal of Social and Humanity Studies, 2018)
In the world of shadow puppet performances, there is a central figure known as puppet master or dalang. Dr. Djoko Santoso who lives in the town of Batu East Java, is a doctor and also a dalang. His uniqueness is to synchronize two different professions by making wayang kulit as health education media. This research was conducted to find out how the process of message design done by dr. Djoko Santoso as the main informant in using wayang kulit as health education media. This research uses interpretive approach with phenomenology type of varization. This study used a key informant, dr. Djoko Santoso selected by purposive sampling. Methods of data collection is done by in-depth interview, direct observation, and documentation. The type of this research is qualitative with descriptive analysis level. The results of this study indicate that the informant performs the message design process before performing a wayang kulit show. The treatment done by the informant in designing the message was then referred to as a pre-show observation. This pre-event observation contains several stages: (1) the location identification phase, (2) the construction phase of the issue, and (3) the cultural understanding phase. Informant tend to use verbal messages that are easy to understand the audience in delivering health education. In non-verbal message design, the speaker creates a wayang with a doctor-style clothing design and a nurse to replace the appereance of traditional costume in the purpose to reinforce the medical impression.Â Â